اللّغة والقيم في الأناشيد المدرسيّة - زيتونة مسعود,علي (University of Eloued جامعة الوادي, 2024)
Abstract: School songs are an important part of the educational process at the primary level. The song, as a poetic poem, has a major role in raising the student. In terms of the linguistic lexicon, and the different values that it reflects. These are the two aspects that this research paper seeks to clarify, in a descriptive and analytical study of the chants of the “Arabic Language” book for the fifth year of primary school. الأناشيد المدرسيّة جزءٌ هامٌّ من العمليّة التربويّة في المرحلة الابتدائية. فالأنشودة باعتبارها قصيدةً شعريّةً، لها دور كبير في تربية التلميذ؛ من حيث المعجم اللّغوي، والقِيَم المختلفة التي تعكسها. وهما الجانبان اللذان تسعى هذه الورقة البحثيّة إلى تبيينهما، في دراسة وصْفيّة تحليليّة لأناشيد كتاب «اللغة العربية» للسنة الخامسة ابتدائي.
دراسة وصفيّة تحليليّة في كتاب «اللغة العربيّة» للسّنة الخامسة ابتدائي
Keywords: التربية; القيم; songs; Fifth primary school; education; language; values